2006
DOI: 10.1172/jci26991
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of stearoyl-CoA desaturase-1 (SCD1) in the onset of diet-induced hepatic insulin resistance

Abstract: Stearoyl-CoA desaturase-1 (SCD1) catalyzes the synthesis of monounsaturated fatty acids from saturated fatty acids. Mice with a targeted disruption of Scd1 gene locus are lean and display increased insulin sensitivity. To examine whether Scd1 activity is required for the development of diet-induced hepatic insulin resistance, we used a sequence-specific antisense oligodeoxynucleotide (ASO) to lower hepatic Scd1 expression in rats and mice with diet-induced insulin resistance. Treatment of rats with Scd1 ASO ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
169
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(187 citation statements)
references
References 53 publications
14
169
2
2
Order By: Relevance
“…There is strong evidence that downregulation of SCD1 prevents or reduces the development of NAFLD, obesity and insulin resistance [29][30][31][32]. Elevated hepatic transcription of Scd1 has been reported in fat-fed mice of the 129S6 [13] and C57BL/6J [13,23] strains.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that downregulation of SCD1 prevents or reduces the development of NAFLD, obesity and insulin resistance [29][30][31][32]. Elevated hepatic transcription of Scd1 has been reported in fat-fed mice of the 129S6 [13] and C57BL/6J [13,23] strains.…”
Section: Discussionmentioning
confidence: 99%
“…Using the hyperinsulinemic-euglycemic clamp method, ASOmediated inhibition of SCD1 was shown to prevent short-term (5-day) high-fat diet-induced hepatic insulin resistance in mice and rats, without affecting whole-body glucose uptake [83]. These effects were observed using both intraperitoneal ASO injection, which affects both liver and adipose, as well as intraportal ASO infusion, which is liver specific [83].…”
Section: The Impact Of Liver Scd1 Deficiency On Obesity and Insulin Rmentioning
confidence: 99%
“…Using the hyperinsulinemic-euglycemic clamp method, ASOmediated inhibition of SCD1 was shown to prevent short-term (5-day) high-fat diet-induced hepatic insulin resistance in mice and rats, without affecting whole-body glucose uptake [83]. These effects were observed using both intraperitoneal ASO injection, which affects both liver and adipose, as well as intraportal ASO infusion, which is liver specific [83]. Short-term ASO-mediated SCD1 inhibition also caused enhanced hepatic insulin signaling, suppression of hepatic gluconeogenic gene expression (Pepck and G6pase) and accumulation of hepatic triglycerides [83].…”
Section: The Impact Of Liver Scd1 Deficiency On Obesity and Insulin Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the knockout (KO) of Acc2 (also known as Acacb) resulted in increased energy expenditure as measured by the volume of oxygen consumed Á V O 2 [7,8]. It has also been shown that inhibition of the downstream genes Scd1 and Dgat2 also lowers Acc1 (also known as Acaca) and Acc2 expression by a feedback mechanism [9][10][11]. These results supported drug research targeted approaches to lower malonyl-CoA.…”
Section: The Premisementioning
confidence: 72%